Highliting the Importance of Business Intelligence Maturity Models in the Healthcare Sector - Silva, João; Gonçalves, Célia Talma; Félix, Catarina (Bobcatsss, 2023)
The digital transformation associated with the huge volume of data that healthcare organizations deal with, nowadays, are on the basis of transforming this complex knowledge-driven industry to transform data into knowledge. The healthcare industry requires comprehensive models to help identifying the priorities to implement a Business Intelligence (BI) solution. Business Intelligence can help organizations make better decisions by showing present and historical data within their business context. In the recent digital transformation, the decision process is supported through data analysis. Established as a common denominator, small and large organizations transform their data into valuable knowledge and powerful capabilities to help them become more data-driven organizations. To become a data-driven organization means that organization leaders/managers make decisions supported on the data that is setting in the organization. The decision support systems together with technology helps the decision makers to gather insights to enhance organizations. This paper presents and highlights a comprehensive review of existing healthcare maturity models and tries to identify the main features of the presented models as well as the common success factors in adopting a Business Intelligence Maturity Model in Healthcare organizations.